Anxiety of Final Semester Students: Mini Review - Dzulfikar Muhammad A; Nafila Hana Rosyidawati; Arista Ayu Sudrajat; Nadia Hasna Khairunnisa; Baiq Dwi Zulfa Rahmawati; Widia Husnul Khatimah; Putri Apriyani; Amalia Putri Dwi Andriani; Putri Anisa Widyastuti; Dhea Silvi Suryani; Putri Faizatus Sholihah Nur Azizah; Dewi Yuniasih (Ahmad Dahlan Medical Journal, 2021)
Students often experience events that may cause anxiety in the final stages of their lectures, especially at the stage of writing a thesis. Our literature review research aims to find out about anxiety in students and its prevention efforts. Approximately 80% of students who experience anxiety during thesis exams are recorded. Our literature research finds that prevention efforts are needed, including increasing individual student awareness to reduce negative thoughts and trying to focus thoughts and attention on positive things. In addition, universities need to provide adequate health facilities, including psychological assistance.